The Effect of Lavender Aromatheraphy on Decreasing of Perineum Paint Pain in Breast Mothers - Anita Indra Afriani; Deny Rahmawati (Media Keperawatan Indonesia, 2019)
Aromatherapy lavender can increase alpha waves in the brain and this gelombang helps to create a relaxed state. Lavender essential oil can reduce anxiety. Type of quantitative descriptive research with Quasi Experimental approach with pretest-posttest design with two groups. The population and sample in this study were all postpartum mothers in Bonang II Public Health Center in June 2018 as many as 30 people with total sampling technique. The statistical test used was the Wilcoxon test. There were differences in perineal wound pain in postpartum mothers before and after lavender aromatherapy was given to the intervention group. There are differences in pain of perineal wounds in postpartum mothers before and after giving jasmine aromatherapy to the control group. There were differences in the reduction of pain in perineal wounds in the intervention group and in the control group. Lavender aromatherapy is more effective in reducing pain compared to jasmine aromatherapi.